The Effect of Macroeconomic Fundamentals, Capital Structure and Technology on Stock Return with Good Corporate Governance and Financial Performance as Intervening Variables: A Study of Manufacturing Companies on the Indonesia Stock Exchange - Pertiwi, Ana; Hwihanus; R. Pandin, Maria Yovita (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This study analyzes the effect of macroeconomic fundamentals, capital structure, and technology on stock return with good corporate governance and financial performance as intervening variables in manufacturing companies on the Indonesia Stock Exchange for the period 2021-2023. The research method uses Partial Least Squares-Structural Equation Modeling (PLS-SEM) with 24 observations from 8 manufacturing companies. Secondary data were obtained from financial statements, annual reports, and official publications. Results show that only 5 out of 18 hypotheses are significant. Good corporate governance has a highly significant effect on financial performance (β=0.799, p=0.000). Macroeconomic fundamentals have a positive effect on good corporate governance (β=0.449, p=0.009). Capital structure has a positive effect on good corporate governance (β=0.513, p=0.021) and financial performance (β=0.307, p=0.001). Good corporate governance mediates the effect of macroeconomic fundamentals on financial performance (β=0.359, p=0.027). Technology has no significant effect on endogenous variables, confirming the Solow Productivity Paradox. The relationship between governance and financial performance with stock return is not significant, indicating market inefficiency.